A novel three dimensional-printed biomechanically evaluated patient-specific sacral implant in spinopelvic reconstruction after total en bloc sacrectomy - Lv, Zhaorui; Li, Jianmin; Yang, Zhiping; Li, Xin; Yang, Qiang; Li, Zhenfeng (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Reconstruction after a total sacrectomy is a challenge due to the special anatomical and biomechanical factors. Conventional techniques of spinal-pelvic reconstruction do not reconstruct satisfactorily. We describe a novel three-dimensional-printed patient-specific sacral implant in spinopelvic reconstruction after total en bloc sacrectomy. Methods: We performed a retrospective cohort study including 12 patients with primary malignant sacral tumors, including 5 men and 7 women with a mean age of 58.25 years (range 20-66 years), undergoing total en bloc sacrectomy with 3D printed implant reconstruction from 2016 to 2021. There were 7 cases of chordoma, 3 cases of osteosarcoma, 1 case of chondrosarcoma, and 1 case of undifferentiated pleomorphic sarcoma. We use CAD technology to determine surgical resection boundaries, design cutting guides, and individualized prostheses, and perform surgical simulations before surgery. The implant design was biomechanically evaluated by finite element analysis. Operative data, oncological and functional outcomes, complications, and implant osseointegration status of 12 consecutive patients were reviewed. Results: The implants were implanted successfully in 12 cases without death or severe complications during the perioperative period. Resection margins were wide in 11 patients and marginal in one patient. The average blood loss was 3875mL (range, 2000–5000 mL). The average surgical time was 520 minutes (range, 380–735 minutes). The mean follow-up was 38.5 months. Nine patients were alive with no evidence of disease, two patients died due to pulmonary metastases, and one patient survived with disease due to local recurrence. Overall survival was 83.33% at 24 months. The Mean VAS was 1.5 (range, 0 to 2). The mean MSTS score was 21 (range, 17 to 24). Wound complications occurred in 2 cases. A deep infection occurred in one patient and the implant was removed. No implant mechanical failure was identified. Satisfactory osseointegration was found in all patients, with a mean fusion time of 5 months (range 3-6 months). Conclusions: The 3D-printed custom sacral prosthesis has been effective in reconstructing spinal-pelvic stability after total en bloc sacrectomy with satisfactory clinical outcomes, excellent osseointegration, and excellent durability.